Bacterial Consortium Biofilm-Based Electrochemical Biosensor for Measurement of Antioxidant Polyphenolic Compounds - Rani Melati Sukma; Dyah Iswantini; Novik Nurhidayat; Mohamad Rafi (Electrochem)
This work describes the development of an electrochemical biosensor method based on bacterial consortia to determine antioxidant capacity. The bacterial consortium used is a combination of bacteria from the genera Bacillus and Pseudomonas which can produce the enzymes tyrosinase and laccase. The consortium bacteria were immobilized on the surface of the screen-printed carbon electrode (SPCE) to form a biofilm. Biofilms were selected based on the highest current response evaluated electrochemically using cyclic voltammetry analysis techniques. Optimum consortium biofilm conditions were obtained in a phosphate buffer solution of pH 7, and biofilm formation occurred on day 7. This work produces analytical performance with a coefficient of determination (R2) of 0.9924. The limit of detection (LOD) and limit of quantification (LOQ) values are 0.5 µM and 10 µM, respectively. The biosensor showed a stable response until the 10th week. This biosensor was used to measure the antioxidant capacity of five extracts, and the results were confirmed using a standard method, the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The highest antioxidant capacity is guava extract and the lowest is tempuyung extract. Thus, the development of this biosensor method can be used as an alternative for measuring antioxidant capacity.